2022
DOI: 10.1098/rsta.2021.0318
|View full text |Cite
|
Sign up to set email alerts
|

Localized bulging of an inflated rubber tube with fixed ends

Abstract: When a rubber tube with free ends is inflated under volume control, the pressure will first reach a maximum and then decrease monotonically to approach a constant asymptote. The pressure maximum corresponds to the initiation of a localized bulge and is predicted by a bifurcation condition, whereas the asymptote is the Maxwell pressure corresponding to a ‘two-phase’ propagation state. By contrast, when the tube is first pre-stretched and then has its ends fixed during subsequent inflation, the pressure as a fun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…6 shows the actual variation of P against ap0q predicted by the 1d model when L is varied and the averaged stretch λ c is fixed or λ c is varied but L is fixed. These results confirm the theoretical prediction of Guo et al (2022) that the right branches of these curves all converge to a master curve that is independent of L or λ c . These curves all terminate at the point where the axial stress near each end of the tube has become compressive enough so that secondary Euler buckling or axisymmetric wrinkling becomes possible.…”
Section: The Case Of Fixed Endssupporting
confidence: 87%
See 1 more Smart Citation
“…6 shows the actual variation of P against ap0q predicted by the 1d model when L is varied and the averaged stretch λ c is fixed or λ c is varied but L is fixed. These results confirm the theoretical prediction of Guo et al (2022) that the right branches of these curves all converge to a master curve that is independent of L or λ c . These curves all terminate at the point where the axial stress near each end of the tube has become compressive enough so that secondary Euler buckling or axisymmetric wrinkling becomes possible.…”
Section: The Case Of Fixed Endssupporting
confidence: 87%
“…It is shown that the bifurcation condition for this case corresponds to the axial force reaching a maximum at a fixed pressure (Fu & Il'ichev, 2015); in other words, as pressure is increased, the critical pressure is the value of pressure at which the axial force reaches a maximum when viewed as a function of the axial stretch. Also, in contrast with the case of fixed axial force where the measured pressure approaches a constant value (the propagation pressure), the measured pressure in the case of fixed ends has an N shape where the right branch approaches a master curve that is independent of the pre-axial-stretch or the tube length (Guo et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Drawing upon recent understandings of localized bulging in inflated tubes and localized necking in stretched cylinders, outlined in Fu et al [35], Emery and Fu [36] Wang et al [43], Guo [44], Emery and Fu [61], we now summarize the deformation evolution of the current problem for three distinct loading conditions by virtue of Figures 8 and 9 as follows.…”
Section: The Maxwell Equal-area Rulementioning
confidence: 99%
“…There, the pressure following bulge initiation decreases to a minimum and then rises again, and the latter is accompanied by bulge propagation. Localized bifurcation of rubber tubes with different end conditions is investigated in Guo et al [44]. In a tube with free ends, bulge initiation occurs at the pressure maximum, followed by a monotonic decrease to approach a constant asymptote.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [21] study the bulging of a rubber tube with fixed ends when it is inflated by internal pressure. Deriving the bifurcation condition for localized bulging is an involved mathematical feat.…”
Section: Contents Of the Theme Issuementioning
confidence: 99%